SOME ASPECTS OF EMPLOYMENT IN ROMANIA’S AGRICULTURE IN THE EUROPEAN CONTEXT - BURJA, Vasile (Annales Universitatis Apulensis Series Oeconomica, 2014)
Employment in agriculture is an important component of the policy of sustainable rural development. This has implications for the effective use of agricultural potential that Romania has in stabilizing rural population by achieving revenue to ensure an adequate quality of life. The analysis presented in this paper highlights common characteristics of employment in agriculture and the disparities recorded in Romania and other countries that joined the European Union later (Poland, Hungary and Bulgaria) against one of the European countries with developed agriculture (Germany). Raised disparities concern especially the high level of employment in agriculture in Romania and low labor productivity, but other features of employment-related to demographics, mode of employment, training and education are analyzed.